A [de]formação da infância na sociedade de consumo : o merchandising na telenovela Carrossel do SBT - Silva, Karen de Cássia (2016)
Advertising aimed at children has become increasingly present in their everyday life. Already in early childhood, boys and girls are bombarded every day by advertisements that intend to seduce them to consume many types of products - toys, clothes, shoes and food - and brands. Within the context of the cultural industry, advertising becomes responsible for the disclosure of a way of living and thinking based on extremely consumerist attitudes, with drastic effects on the formation of the subject in that it makes damage in their subjectivity and makes it hostage of profit maximization. Thus, this research aims to investigate the merchandising occurred in Soap Opera "Carrossel" from television channel SBT based on Critical Theory. Education is essential to seek the emancipation of individuals, because the right of people to clarify and become subject endowed with autonomy and criticality would be greater if they could make their sociocultural inclusion of choices beyond the consumer field.